Genetic variants of Orientia tsutsugamushi identified from scrub typhus cases in Malaysia - Zan, H.A.M.; Ponnampalavanar, S.; Omar, S.F.S.; Savithiri, P.D.; Lim, Y.A.L.; Tay, S.T. (Malaysian Society for Parasitology, 2016)
We report herein the clinical presentation and diagnosis of scrub typhus in three patients attending a teaching hospital in Malaysia. Three genetic variants belonged to the Karp and Gilliam strains of O. tsutsugamushi were amplified from the acute blood samples of the patients by a nested polymerase chain reaction assay. The circulation of different genetic variants of O. tsutsugamushi strains might complicate the presentation and severity of scrub typhus. Loop-PCR is a promising diagnostic tool for rapid diagnosis of scrub typhus.